2005
DOI: 10.1007/s11248-005-0439-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of dextran in transgenic potato plants

Abstract: The production of dextran in potato tubers and its effect on starch biosynthesis were investigated. The mature dextransucrase (DsrS) gene from Leuconostoc mesenteroides was fused to the chloroplastic ferredoxin signal peptide (FD) enabling amyloplast entry, which was driven by the highly tuber-expressed patatin promoter. After transformation of two potato genotypes (cv. Kardal and the amylose-free (amf) mutant), dextrans were detected by enzyme-linked immunosorbent assay (ELISA) in tuber juices of Kardal and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…Similar observations were made for Kardal and amf potato transformants expressing the Leuconostoc mesenteroides DSRS gene (Kok-Jacon et al 2005b). With this study, we provide a second example that the amf background might be less suitable for the production of carbohydrate polymers or oligomers from sucrose.…”
Section: Granule Targeting Of Gtficat Without Covalent Attachment Of supporting
confidence: 82%
See 3 more Smart Citations
“…Similar observations were made for Kardal and amf potato transformants expressing the Leuconostoc mesenteroides DSRS gene (Kok-Jacon et al 2005b). With this study, we provide a second example that the amf background might be less suitable for the production of carbohydrate polymers or oligomers from sucrose.…”
Section: Granule Targeting Of Gtficat Without Covalent Attachment Of supporting
confidence: 82%
“…Internodal stem segments from the tetraploid (cv. Kardal (KD)) and diploid mutant (amf) potato genotypes were used for Agrobacterium-mediated transformation, which was performed as described by Kok-Jacon et al (2005b).…”
Section: Preparation Of Constructs Containingmentioning
confidence: 99%
See 2 more Smart Citations
“…Its high molecular weight and heterogeneity made it impossible to resolve on a HPLC column which provides a more direct assay to measure polymers with a low degree of polymerization (Sevenier et al 1998; this study). Kok-Jason et al (2005) reported a method to detect dextrans in transgenic corn seeds with ELISA (enzyme-linked immunosorbent assay) using a monoclonal anti-a-(1fi6) dextran antibody that recognizes the terminal non-reducing end of the polysaccharide. Our glucan quantification method took the advantage of the high percentage of a-(1fi6) and the low percentage of a-(1fi4) linkages present in the GTF-D glucan.…”
Section: Discussionmentioning
confidence: 99%